Dose response of visible color center radiophotoluminescence in lithium fluoride crystals irradiated with a reference 60Co gamma beam in the 1–20 Gy dose range. (February 2022) - Piccinini, M.; Nichelatti, E.; Pimpinella, M.; De Coste, V.; Montereali, R.M.
Abstract: The visible radiophotoluminescence response of radiation-induced stable F2 and F3 + color centers in nominally pure lithium fluoride crystals, irradiated with a reference 60 Co gamma beam in the 1–20 Gy dose range, was carefully investigated. After irradiation, the Stokes-shifted emission spectra of the colored crystals were measured as a function of time under continuous laser excitation at 445 nm and in stationary conditions. The F2 radiophotoluminescence intensity remains constant; the signal, spectrally integrated in a 50 nm-wide interval centered on the F2 emission peak at 670 nm, exhibited a linear dependence on the absorbed dose with a good signal-to-noise ratio, stability for multiple readout and long storage times. Combined with our previous investigations after irradiation at similar doses with low-energy protons and clinical X-ray beams, these experimental results confirm the feasibility of passive solid-state dosimeters for radiotherapy based on color center radiophotoluminescence in nominally pure lithium fluoride crystals. Highlights: Time evolution of F2 and F3 + color-center RPL under CW laser excitation is reported. F2 color-center RPL in laser-excited γ-treated LiF is linear with dose up to 20 Gy. The RPL signal shows no significant fading within a time interval of 39 months. The signal-to-noise ratio on the RPL peak of F2 color centers is 9.4 at 1 Gy dose.